Impossible Individuality : Romanticism, Revolution, and the Origins of Modern Selfhood, 1787-1802 - Izenberg, Gerald N. (Book collections on Project MUSE., 2001)
Studying major writers and philosophers--Schlegel and Schleiermacher in Germany, Wordsworth in England, and Chateaubriand in France--Gerald Izenberg shows how a combination of political, social, and psychological developments resulted in the modern concept of selfhood. More than a study of one national culture influencing another, this work goes to the heart of kindred intellectual processes in three European countries. Izenberg makes two persuasive and related arguments. The first is that the Romantics developed a new idea of the self as characterized by fundamentally opposing impulses: a dri.